Madam Spry and Mr Mustard - "Coeley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Violet Spry, the very sly spy, has a red leather spy suit with thirteen pockets, fly-foot boots for walking down walls, and green jellybeans for moments of hunger. She faces her biggest challenge yet in Mr Mustard, the master illusionist turned bully. Will Madam Spry-and her faithful hound Hugo-be able to foil his frightening FX?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Detective and mystery fiction